Digitalni avtor? - Hartling, Florian (Primerjalna književnost, 2009)
Since the birth of the World Wide Web as the most successful application of the Internet there have been hopes of literary theorists (Landow, Bolter) that the new digital media would finally allow for the "death of the author" and the birth of the "writing reader". The hypertext as new genre of text seemed to be powerful enough to fulfill the older hopes of the poststructuralists (Barthes, Foucault). Although these euphoric hopes have been abandoned by literary theory for the most part, the Internet in the actual literary production still seems to have the power to be an "authorless" media in principle: In the oft-discussed encyclopaedia "Wikipedia" the collaborative written text supposedly is more important than the authors. Literary experiments in the digital media are exploring how text can be written just by text-algorithms. These projects finally do not need writers anymore, they are using data taken from search engines. But this somewhat naive idea of an "authorless" digital media clearly can be refuted. First, the author has been revived by the new media and continues to thrive within it. Second, in contrast to the prediction of huge "authorless" collaborative text-production in online journalism, it is hard to find any collaborative works of literature. Third, even with collaborative projects or "codeworks" the function of an author does not disappear but is spread over different persons, which can even lead to a "dissociated" authorship. The author cannot disappear or "die" in the Internet, because its characteristics will not allow this to happen. Therefore the Internet does not stand for the "death" of the author: it actually appears to be a fountain of youth for literary authorship instead. These findings are discussed using recent experiments with authorship in digital literature.
Keywords: literatura in tehnologija; digitalna literatura; medmrežje; avtor; avtorstvo